Dynamics of the implementation of the protective role in the conduct of crimes: the practice of the Convention for the Protection of Human Rights and Fundamental Freedoms - Balobanova, Dariia; Gorbachova, Iryna; Otsyatsya, Anastasiia; Dmytruk, Mykhailo; Khylchenko, Anastasiia (Cuestiones Políticas, 2020)
Criminal law offers the possibility of interfering with human life. To avoid such unjustified interference, society and the state must guarantee that human and civil rights are protected and that the standards established in the Convention for the Protection of Human Rights and Fundamental Freedoms are observed. Therefore, it is important to analyze the dynamics of the implementation of the protective function in the conviction of crimes in the interpretation of the European Court of Human Rights ECHR. In the methodological, he made of dialectics and documentary observation. The work aims to analyze the practice of the European Court of Human Rights, which tracks the dynamics of the protection function in sentencing for crimes. As a result of the study, the dynamics of the protection function in sentencing for criminal offenses were clarified through the practice of the ECHR, the problematic issues of the implementation of the protection function were analyzed in the example of Ukraine and foreign countries, and proposals were made, to use the practice of the ECHR as a “living tool” for the protection of human and civil rights and freedoms.